Сайлаубаева М., Атамбаева Ш.А., Ниязова Р.Е. Гены и miRNA, ответственные за репродуктивность сельскохозяйственных животных: Нaучно-исследовaтельский институт проблем биологии и биотехнологии, Кaзaхский нaционaльный университет им. aль-Фaрaби, Кaзaхстaн, г. Алмaты (Eurasian Journal of Ecology, 2018)
In this study, the binding of miRNA to mRNA genes responsible for the reproductivity of farm animalswas studied. It was identified 39 genes responsible for the productivity of Bos taurus (cow), Bos mutus(yak), Gallus gallus (chicken), Sus scrofa (pig), Capra hircus (goat), Equus caballus (horse) and Ovis aries(sheep) farm animals and binding there mRNAs with miRNAs was studied. It was found 65 binding sites for63 miRNAs. From thus, 29 binding sites are located in the CDS, 11 - in the 5’UTR and 40 - in the 3’UTR.Some miRNAs have multiple binding sites with mRNA of genes responsible for the productivity of farmanimals. EGF gene has thirteen binding sites, RYR1 has twelve binding sites, THRSP has eight binding sites,FASN has eight binding sites, HIF1AN has eight binding sites, PIK3R1 has seven binding sites, SCD1 hassix binding sites. miR-3195 binds with PIK3R1 gene mRNA with ΔG/ΔGm value equal to 96%, miR-3141,miR-466, miR-7162-3p binds with genes MFGE8, GDF9, CAST with ΔG/ΔGm value equal to 95-96%.Key words: miRNA, mRNA, binding sites, target genes.